The Use of the Harmonium in Opera - FAZAKAS, Ádám Sándor (Studia Universitatis Babes-Bolyai Musica, 2024)
The article explores the role of harmonium in opera during the transformative 19th and early 20th centuries, amidst significant reforms in orchestration. The author thoroughly explores how harmonium is used in opera, even providing a table of operas that feature this instrument. It delves into specific opera passages by composers representing diverse nationalities and spanning various epochs, covering the period from 1845 to 1936. Through examples from works such as Verdi’s “Giovanna d’Arco” and “Don Carlos,” Dvořák’s “Rusalka,” and Enescu’s “Œdipe,” the essay illustrates the diverse roles played by the harmonium in operas. The author highlights the historical and musical significance of the harmonium in opera, suggesting a reevaluation of its role in today’s performances.